Mitapivat metabolically reprograms human β-thalassemic erythroblasts, increasing their responsiveness to oxidation - Angela Siciliano; Angelo D’Alessandro; Alessandro Matte; Giovanni Bisello; Mariarita Bertoldi; Monika Dzieciatkowska; Amy Argabright; Richard Huot Pozzetto; Veronica Riccardi; Andrea Mattarei; Alberto Ongaro; Jacopo Ceolan; et al. (Blood Advances)
Abstract: β-thalassemia (β-thal) is a worldwide hereditary red cell disorder characterized by severe chronic anemia. Recently, the pyruvate kinase (PK) activator mitapivat has been shown to improve anemia and ineffective erythropoiesis in a mouse model of β-thal and in patients with non–transfusion-dependent thalassemia. Here, we showed that in vitro CD34+-derived erythroblasts from patients with β-thal (codb039) are characterized by persistent expression of 2 PK isoforms, PKR and PKM2, compared with healthy cells. Activation of PKR and PKM2 via mitapivat promoted significant metabolic reprogramming of β-thal erythroblasts, resulting in higher levels of high-energy phosphate compounds, including adenosine triphosphate (ATP) and triphosphate nucleoside pools. Proteomics analyses revealed an accumulation of PKR, suggesting a possible beneficial effect of mitapivat on the stability of PKs. Increased ATP availability was accompanied by a higher degree of protein phosphorylation, especially in proteins involved in cell cycle regulation at the transcriptional, translational, and posttranslational levels, supporting the effect of mitapivat on erythroid maturation. Upon treatment with mitapivat, β-thal erythroblasts showed decreased markers of oxidation, including cysteine oxidative posttranslational modifications, downregulation of heat shock protein 70 and peroxiredoxin-2 expression, and normalization of the redox-dependent subcellular distribution of the latter enzyme. Collectively, our data support a protective effect of mitapivat in β-thal erythropoiesis, an effect favored by its activation of persistently expressed PKR and PKM2. In addition to the anticipated benefits on energy metabolism, we report that mitapivat treatment mitigated the oxidative damage in β-thal erythropoiesis, ensuring improved β-thal erythroblast maturation and survival.